Research on the Technology of Plugging Gushing Water in the Vertical Shaft under Complicated Conditions - Chuanyang Jia; Hailong Wang; Haiquan Liu; Guibin Zhang; Kaihua Sheng (Geofluids)
The shaft is the throat of the mine construction, and it is easily disturbed by gushing water, which affects the mine construction progress. Aiming at technical problems under complex hydrogeological conditions in coal mines, such as vertical shaft lining rupture and serious gushing water, single-liquid and double-liquid cement grouting materials are invalid for multiple plugging of gushing water. Combining with geological data to analyze the conditions of the aquifers and water-blocking layer in the shaft, adopting the multifunctional digital electrical method and digital flow measuring instrument can accurately grasp the flow direction and flow velocity and further obtain the aquifer parameters of the main and auxiliary shafts. At the same time, based on the FLAC numerical simulation software, research on the stress, displacement, and plastic failure of the shaft surrounding rock under different water pressures (0.5 times, 1 time, and 2 times the hydrostatic pressure) and comparative analysis of the influence of the water bodies on the shaft surrounding rock are carried out. On this basis, the following are the objectives: (1) research the mechanical properties of polymer chemical material Malisan N and the mechanism of grouting to plugging gushing water and strengthening surrounding rock, (2) formulate the grouting drilling layout and construction technology for the topsoil and bedrock section of the main and auxiliary shafts, and (3) carry out long-term monitoring of the water inflow. The monitoring data showed that the measured water inflow was less than 0.05 m3/h after the grouting of the shaft surrounding rock, which achieved the purpose of preventing the shaft linings from rupturing, plugging the gushing water, and stabilizing the aquifer water pressure.